Complicaciones postoperatorias en prótesis de cadera en adultos mayores: evaluación de la atención integral - Monar Sánchez, Darwin Israel (2025)
Hip prosthesis is a common procedure in older adults to treat osteoarthritis and other conditions, like any surgery, there are risks of postoperative complications. Therefore, the objective of this article was to evaluate the comprehensive care of nursing staff in the faceof frequent complications of older adult patients with hip prosthetics in the surgical recovery room in Ecuador, through a qualitative methodology, with bibliographic and exploratory review through the PRISMA method, with a review of 35 articles, where the main results were to improve the practises, interventions and the most up-to-date recommendations for better care for post-surgical patients with hip prosthesis. This includes the identification of barriers that hinder the implementation of key practises, as well as the unmet needs of patients during their recovery process, evaluating scientific knowledge in the field of postoperative care, promoting a higher quality of care, safety, and patient recovery. The importance of developing critical thinking on the part of nursing staff was identified, to achieve these goals in the application of the care map in the nursing careveprocess, allowing the nurse to make wise decisions. As a conclusion, the value of nursing in the recovery process of patients with surgical alterations can be appreciated, by promoting asatisfactory response of the patient in these interventions carried out by the nursing team in the recovery room.